2023
DOI: 10.1021/acsaem.2c03897
|View full text |Cite
|
Sign up to set email alerts
|

Phenanthroimidazole-Based Covalent Organic Frameworks with Enhanced Activity for the Photocatalytic Hydrogen Evolution Reaction

Abstract: The rational design of organic semiconductors based on crystalline covalent organic frameworks (COFs) as efficient photocatalysts is highly desirable. In this study, the first example of phenanthroimidazole-based COFs is reported: PIm-COF1 with an imine linkage and PIm-COF2 with a β-ketoenamine-linkage. Both COF materials showed substantial optical properties. The average hydrogen evolution rate was 7417.5 μmolg −1 h −1 for PIm-COF2, which was 14 times higher than that of PIm-COF1 (528.5 μmolg −1 h −1 ). This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…We further assessed the dissociation efficiency of the electron–hole pairs using electrochemical impedance spectroscopy (EIS). Nyquist plots showed reduced charge transport resistance after light irradiation for all samples, likely due to the increased charge density by photoexcitation (Figure b) . More importantly, the decrease in transport resistance for EFB-MOF was most pronounced among the samples, indicating a very rapid photoinduced charge transport capability by efficient exciton separation.…”
Section: Results and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We further assessed the dissociation efficiency of the electron–hole pairs using electrochemical impedance spectroscopy (EIS). Nyquist plots showed reduced charge transport resistance after light irradiation for all samples, likely due to the increased charge density by photoexcitation (Figure b) . More importantly, the decrease in transport resistance for EFB-MOF was most pronounced among the samples, indicating a very rapid photoinduced charge transport capability by efficient exciton separation.…”
Section: Results and Discussionmentioning
confidence: 95%
“…Nyquist plots showed reduced charge transport resistance after light irradiation for all samples, likely due to the increased charge density by photoexcitation (Figure 5b). 58 More importantly, the decrease in transport resistance for EFB-MOF was most pronounced among the samples, indicating a very rapid photoinduced charge transport capability by efficient exciton separation. These results align with the calculated exciton binding energy, emphasizing the pivotal role of fluorine in enhancing the photocatalytic efficiency, which was enabled by our material platform.…”
Section: ■ Introductionmentioning
confidence: 93%
“…Adopting this strategy, a variety of COFs have been prepared. [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] For example, Yang et al designed PETZ-COF via the solvothermal reaction of electron-donating 4PE-4NH 2 and electron-deficient TZTZ-2BA for photocatalytic H 2 generation. As a comparison, a COF (PEBP-COF) without D-A moieties was also constructed using 4PE-4NH 2 to react with BP-2BA (Fig.…”
Section: Structure Engineeringmentioning
confidence: 99%
“…Enhancing photocatalytic performance involves constructing a Donor (D)-Acceptor (A) structure within the photocatalyst, facilitating the spontaneous transfer of charges from D to A. 27,28 Previous research has demonstrated that D-A structures effectively reduce the band gap, enhance charge transfer rates, and prolong carrier lifetimes. [29][30][31] Additionally, incorporating π units can impact the electron acceptor domain, expediting charge transfer and the migration of photoexcited electrons.…”
Section: Introductionmentioning
confidence: 99%